2014
DOI: 10.1128/mcb.00231-14
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Siderophore 2,5-Dihydroxybenzoic Acid Deficiency Promotes Anemia and Splenic Iron Overload in Mice

Abstract: Eukaryotes produce a siderophore-like molecule via a remarkably conserved biosynthetic pathway. 3-OH butyrate dehydrogenase (BDH2), a member of the short-chain dehydrogenase (SDR) family of reductases, catalyzes a rate-limiting step in the biogenesis of the mammalian siderophore 2,5-dihydroxybenzoic acid (2,5-DHBA). Depletion of the mammalian siderophore by inhibiting expression of bdh2 results in abnormal accumulation of intracellular iron and mitochondrial iron deficiency in cultured mammalian cells, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
1
31
0
3
Order By: Relevance
“…In particular, recent evidence indicates that 2,5-DHBA (2,5-dihydroxy benzoic acid) is an important mammalian siderophore. 31,32 The role of 2,5-DHBA and the enzyme, 3-hydroxybutyrate dehydrogenase-2, involved in 2,5-DHBA biosynthesis needs to be evaluated in ICH.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent evidence indicates that 2,5-DHBA (2,5-dihydroxy benzoic acid) is an important mammalian siderophore. 31,32 The role of 2,5-DHBA and the enzyme, 3-hydroxybutyrate dehydrogenase-2, involved in 2,5-DHBA biosynthesis needs to be evaluated in ICH.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that bdh2 is a critical regulator of the siderophore 2,5-DHBA and that its absence results in complete abrogation of 2,5-DHBA biogenesis in cultured cells, yeast, zebrafish embryo, and mice (18,20). We also found that bdh2 inactivation results in hypohemoglobinization and reduced erythrocyte maturation in zebrafish embryos (18).…”
Section: Resultsmentioning
confidence: 51%
“…Interestingly, 2,5-DHBA is synthesized by an evolutionarily conserved pathway, and BDH2, a homolog of bacterial EntA, catalyzes a rate-limiting step (18). Knockdown of bdh2 results in siderophore depletion and as a consequence confers heme deficiency, an iron-dependent mitochondrial process, in cultured cells, yeast, zebrafish, and mice (18,20). We also found that bdh2 inactivation increased erythrocyte immaturity in zebrafish embryos.…”
Section: Significancementioning
confidence: 62%
See 2 more Smart Citations